Gambaran Asupan Zat Gizi Makro dan Status Gizi Ibu Hamil di Wilayah Puskesmas Parit Mayor Kecamatan Pontianak Timur Kota Pontianak - desi, desi; Intan, Shela Sri; Rafiony, Ayu; ulfa, mauliana (NUTRITURE JOURNAL; Vol 3 No 1 (2024): Nutriture JournalDO - 10.31290/nj.v3i1.4298, 2024)
Background: Chronic Energy Deficiency (CED) refers to a condition in which a pregnant woman experiences prolonged insufficient food intake, resulting in various health disorders for both the pregnant woman and the developing fetus. The consequences of CED can have negative impacts on the health of the mother and the growth of the fetus. The pregnancy phase is considered a critical period that significantly influences the future quality of human life. Based on Riskesdas data, the proportion of CED risk in pregnant women in West Kalimantan in 2018 reached 13.9%. Objective: To determine the Overview of Macronutrient Intake and Nutritional Status of Pregnant Women in the Parit Mayor Health Center Area. Method: This study utilized a descriptive research design with a cross-sectional approach. The study sample consisted of pregnant women in the Parit Mayor health center area, and the variables examined included nutritional status and macronutrient intake. Univariate analysis was employed. Results: The research findings revealed that the nutritional status of pregnant women based on anthropometry, measured using Mid-Upper Arm Circumference (MUAC), showed a normal category in 68.3% of cases, while 31.7% were categorized as having Chronic Energy Deficiency (CED). Energy intake was insufficient in 58.5% of cases, adequate in 41.5%, protein intake was adequate in 46.3%, insufficient in 29.3%, and excess in 24.4%. Fat intake was insufficient in 61.0%, categorized as adequate in 31.7%, while carbohydrate intake was insufficient in 85.4%, and adequate in 14.6%. Conclusion: Based on the research findings, the majority of pregnant women demonstrate normal nutritional status according to LILA anthropometric measurements with adequate protein intake, although energy, fat, and carbohydrate intake appear to be insufficient. Keywords: Pregnant Women, Nutritional Status, Nutrient Intake